40‐3: Invited Paper: A Large RGB‐achromatic Metalens for Virtual/Augmented Reality Applications. Issue 1 (25th September 2020) - Li, Zhaoyi; Lin, Peng; Huang, Yao-Wei; Park, Joon-Suh; Chen, Wei-Ting; Shi, Zhujun; Cheng, Ji-Xin; Capasso, Federico
Abstract : In this talk, we will present a new platform for a virtual/augmented reality system based on a metalens and a fiber scanning display. The metalens was designed for achromatic focusing of blue, green, and red light. The fiber scanning display features combined desired merits of high resolution, high brightness, high dynamic range and wide color gamut.